Systematic content analysis of self-help smokeless tobacco cessation smartphone applications available in India - Nishant Nishant; Arpit Gupta; Richa Shrivastava; Arpita Rai; Diptajit Das; Ashima Goyal (Journal of Oral Biology and Craniofacial Research)
Background: The content of smartphone applications (apps) that offer smoking cessation interventions has been appraised in the past. Considering the high prevalence of smokeless tobacco (SLT) use in Southeast Asia, identifying high-quality and credible apps for SLT cessation would be more helpful. Objective: This study evaluated the technical quality of apps for SLT cessation and their content adherence with the standard tobacco cessation guidelines. Materials and methods: A systematic search of SLT cessation smartphone apps freely available in the Google PlayStore was conducted using nine relevant search terms, and the first fifty apps under each search term were identified. The technical quality of the apps was rated using the Mobile App Rating Scale (MARS). Adherence of the app content to the standard tobacco cessation guidelines was also determined. Results: Three apps were found to be relevant for SLT cessation. However, none of the apps was high-quality or incorporated existing evidence on SLT cessation. Conclusion: Adherence of these apps to the tobacco cessation guidelines by the National Tobacco Control Program (NTCP), India and the National Institute for Health and Care Excellence (NICE), U.K., was limited only to a few checklist parameters.